Experimental Comparability Among Different Accelerated Reinforced Steel Concrete Corrosion Methods - Sadiq Radhi, Mushtaq; S. Hassan, Maan; N. Gorgis, Iqbal (International Journal of Engineering and Technology, 2018)
The objective of this paper is to inspect the effect of changing the density of the impressed current and wetting-drying condition on accelerated corrosion of reinforced concrete specimens by a galvanostatic method.  Small-scale reinforced concrete columns were prepared and then artificially corroded by different setups of accelerated corrosion under an impressed current and also under different wetting-drying cycles for comparison. The density of the impressed current ranged between 50 and 500 µA/cm2 with different wetting-drying cycles periods. Corrosion current, and cracking were monitored throughout the accelerated corrosion period to determine the level of damage caused by the development of expansive reinforcement steel corrosion products, appearance of the first crack, and pattern of cracking.The results indicated that the galvanostatic method with wetting-drying sequences can be utilized effectively to simulate the normal corrosion of steel reinforcement in the concrete structure. The usage of different intensities of the current has no influence on the crack pattern. Though, increasing the current level leads to a substantial increase in the crack width due to corrosion of the steel reinforcement in a shorter time.